Injuries in women's international ice hockey: an 8-year study of the World Championship tournaments and Olympic Winter Games. Issue 22 (7th July 2015) - Tuominen, Markku; Stuart, Michael J; Aubry, Mark; Kannus, Pekka; Tokola, Kari; Parkkari, Jari
Abstract : Background: We report the incidence, type, mechanism and severity of ice hockey injuries in women's international ice hockey championships. Methods: All injuries in the International Ice Hockey Federation World Women's Championship, World Women's under-18 Championship and Olympic Winter Games tournaments were analysed over an 8-year period using a strict injury definition, standardised reporting and team physician diagnosis. Results: 168 injuries were recorded in 637 games over an 8-year period resulting in an injury rate (IR) of 6.4 per 1000 player-games and 22.0/1000 player-game hours. The IRs were 2.7/1000 player-games for the lower body, 1.4 for the upper body, 1.3 for the head and face and 0.9 for the spine and trunk. Contusion was the most common injury followed by a sprain. The most commonly injured site was the knee (48.6% of lower body injuries; IR 1.3/1000 player-games). The Medial collateral ligament sprain occurred in 37.1% and ACL rupture in 11.4% of knee injuries. A concussion (74.3%; IR 1.0/1000 player-games) was the most common head injury. Conclusions and recommendations: The risk of injury to female ice hockey players at World Championship and Olympic tournaments was about half of that observed in the men's Championships. Full facial protection decreases the risk of lacerations and should be continued in all future female tournaments. More effective prevention strategies for knee, ankle and shoulder injuries are needed in women's ice hockey. Improved concussion education is necessary to promote more consistent diagnosis and return to play protocols.